Design and Implementation of a Web-Based Camping Reservation System A Case Study at Gayo Camping Ceria - Ramadhani; Elfisa; Ferdinal Fikri; Rachmad Ikhsan; Zulfadli (Politeknik Aceh, 2025)
Nature-based tourism is increasingly popular with the public, especially after the COVID-19 pandemic, because it is considered safer, healthier, and closer to nature. One popular form of nature tourism activity is camping. Gayo Camping Ceria, as a nature tourism business in Takengon, Central Aceh, provides tent and camping equipment rental services at affordable prices. However, in its operations, the reservation process and rental management are still carried out manually via WhatsApp and social media, which causes various obstacles such as late confirmations, recording errors, difficulty monitoring stock, and the absence of a centralized documentation system. To address these challenges, this study aims to design and implement a web-based camping reservation system that can automate the entire booking and rental process. The system development methodology uses the Waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and evaluation. The implementation results show that the system successfully meets all functional and non- functional user requirements. The results of the system testing using the black-box testing method indicate that all features run well according to the designed specifications and scenarios. Every process flow, from booking to payment verification, can be executed smoothly. This system has been proven to improve operational efficiency, minimize recording errors, and provide convenience and transparency for both users and administrators. This system not only improves the operational efficiency of Gayo Camping Ceria but also provides a better digital experience for customers. Furthermore, this system has the potential to be adopted by other MSMEs in the nature tourism sector that face similar challenges in managing reservations and rentals. Thus, this research makes a real contribution to the application of information technology to strengthen the digital-based local tourism sector to support sustainable digital transformation.